Performance test and analysis of the first large-scale cable-in-conduit conductor with high Jc Nb3Sn strand for fusion reactor. (22nd February 2021) - Dai, Chao; Wu, Yu; Li, Jiangang; Guo, Zichuan; Qin, Jinggang; Long, Feng; Nijhuis, Arend; Bruzzone, Pierluigi; Stepanov, Boris; Shi, Yi; Liu, Sheng; Zhang, Yongliang; et al.
Abstract: The Comprehensive Research Facility for Fusion Technology (CRAFT) project has been launched in 2019, for developing the essential engineering technologies for Chinese Fusion Engineering Testing Reactor (CFETR). Within this project, a full-size toroidal field (TF) coil will be built as the prototype coil for CFETR. Based on design of CFETR magnet system, the TF coil will operate at 95.6 kA in a peak field of 14.5 T. The high- J c Nb3 Sn strand is taken into consideration due to the critical current density of ITER-grade Nb3 Sn is too low at 14.5 T. Considering that it will be the first time to apply the high- J c Nb3 Sn strand in the large-scale cable-in-conduit conductor (CICC) for fusion magnet, a conductor sample made of high- J c Nb3 Sn strand with short twist pitch (STP) cable pattern was manufactured in ASIPP and tested in SULTAN facility, to investigate the feasibility. The test campaign focuses on the impact of cyclic electromagnetic (EM) loading and warm-up cool-down (WUCD) to the performance of the conductor, the strain distribution of the conductor before and after EM cycles was measured by inductive method to make a deeper insight of the conductor performance evolution. AC losses tests have also been carried out, providing relevant information for further coil design.